A silica supported tricarbocyanine based pH nanosensor with a large Stokes shift and a near infrared fluorescence response: performance in vitro and in live cells - Toum Terrones, Yamili (2017)
We report the synthesis of a near-infrared (NIR) fluorescent pHprobe with a remarkable Stokes shift reported (∼ 135 nm) basedon a tricarbocyanine (Cy-PIP). The fluorescent molecule wasanchored to SiO2 nanoparticles (Cy-PIP@SiO2) and is capable ofmonitoring pH changes within the physiological range (pH 6-8).The Cy-PIP@SiO2 nanoparticles were succesfully internalized byHeLa cells as shown by fluorescence confocal microscopy, whileflow cytometry revealed pH fluctuations during the endocytic pathway.